A four-directional non-fullerene acceptor based on tetraphenylethylene and diketopyrrolopyrrole functionalities for efficient photovoltaic devices with a high open-circuit voltage of 1.18 V. Issue 55 (6th June 2016) - Rananaware, Anushri; Gupta, Akhil; Li, JingLiang; Bilic, Ante; Jones, Lathe; Bhargava, Suresh; Bhosale, Sheshanath V.
Abstract : A four-directional non-fullerene electron acceptor provided a PCE of 3.86% with an excellent high V oc of 1.18 V with the archetypal donor P3HT. Abstract : Through the conjunction of tetraphenylethylene and diketopyrrolopyrrole functionalities, a novel four-directional non-fullerene electron acceptor (denoted as 4D) was designed, synthesized and characterized. The new chromophore is highly soluble (for instance >30 mg mL −1 in o -dichlorobenzene), thermally stable, and exhibits energy levels matching those of the conventional and routinely used donor polymer poly(3-hexyl thiophene). A power conversion efficiency of 3.86% was obtained in solution-processable bulk-heterojunction devices with a very high open circuit voltage of 1.18 V.